FROM SILENCE TO SPEECH: STRATEGIES FOR OVERCOMING SPEAKING ANXIETY IN EFL LEARNERS - Ergasheva Ozodabonu Bahodirjon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: Speaking anxiety is a widespread psychological barrier among English as a Foreign Language (EFL) learners, often hindering oral fluency and participation in communicative tasks. This article explores the root causes of speaking anxiety and identifies evidence-based strategies for mitigating its effects. Based on a mixed-methods study involving surveys and interviews with EFL students and teachers, the findings reveal that affective factors such as fear of judgment, lack of confidence, and linguistic insecurity are the main contributors to speaking anxiety. The study suggests a range of practical solutions including the use of collaborative activities, psychological support techniques, and teacher-led scaffolding approaches.